2018
DOI: 10.1002/jsfa.8851
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory effect of pepsin enzymatic extract from Porphyra yezoensis on murine splenocytes

Abstract: Taken together, these results suggest that PPEE has an immune stimulatory effect on macrophages, dendritic cells, and memory T cells. This property signifies the potential medicinal value of PPEE in clinical implications for immune-compromised diseases. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In a case-control study of breast cancer in South Korea, Yang et al (2010) reported the daily intake of several species of Pyropia (as Porphyra), to be inversely associated with the risk of developing cancer. Pyropia ('gim' in Korea) is commonly eaten dried and roasted (Herath et al 2018;Jung & Choe 2017). A cohort of 362 women with histologically confirmed breast cancer (aged 30-65), and 362 control participants of equal age and menopausal status, completed a food frequency questionnaire for 12 months containing 121 food items, including seaweed.…”
Section: Cancermentioning
confidence: 99%
“…In a case-control study of breast cancer in South Korea, Yang et al (2010) reported the daily intake of several species of Pyropia (as Porphyra), to be inversely associated with the risk of developing cancer. Pyropia ('gim' in Korea) is commonly eaten dried and roasted (Herath et al 2018;Jung & Choe 2017). A cohort of 362 women with histologically confirmed breast cancer (aged 30-65), and 362 control participants of equal age and menopausal status, completed a food frequency questionnaire for 12 months containing 121 food items, including seaweed.…”
Section: Cancermentioning
confidence: 99%
“…It contains a diverse repertoire of immune cells such as macrophages, dendritic cells, T and B lymphocytes and more importantly, both innate and adaptive immune processes appear in it, rendering immune reactions in splenocytes a reliable surrogate of the immune responses in the host in general (Wluka & Olszewski, 2006). A recent study also found that Porphyra yezoensis enzymatic extract increases the proliferation of murine splenocytes (Herath et al, 2018).…”
Section: Discussionmentioning
confidence: 88%
“…The modulation of cell proliferation by MC and/or PM was measured using 3 H-thymidine incorporation assay as previously described [ 47 ]. MLE-12 cells (1 × 10 4 cells/well) seeded in triplicates on 96-well plates (Nunc) were exposed to either varying concentrations (0, 3.9, 7.8, 15.6, 31.3, 62.5, 125, and 250 µg/mL) of MC or PM alone or varying concentrations of PM together with selected concentrations of MC (0, 31.3, and 62.5 µg/mL) for 54 h. After adding 1 μCi of 3 H-thymidine (42 Ci/mmol specific activity), cells were incubated for 18 h, and then harvested on glass fiber filters to determine the amount of thymidine incorporated into DNA using a liquid scintillation spectrometer (Wallac Micro Beta ® TriLux, Perkin Elmer, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%